Helmintos gastrointestinais de jacarés Caiman crocodilus crocodilus Linnaeus, 1758 provenientes da Amazônia Brasileira . - Mazzinghy, Cristiane Lopes (Universidade Federal do Tocantins, 2023)
The breeding of alligators is a way to prevent illegal and indiscriminate hunting of these species and represents a profitable business because the consumption of meat and leather in the international market. One of the species widely adopted for captive holding is Caiman crocodilus crocodilus, alligator of the Amazon. The parasitosis can be an obstacle to the good development from the activity, effecting the infected animal’s survival and the performance, causing meddling between body weight and performance and it is known that crocodilians are infected by species of nematodes, trematodes, pentastomids and Acanthocephala, so few studies are developed with alligators in Brazil. Thus, given the lack of papers about helminthological identification in crocodilians in Brazil and the importance of this datas, for both the record and for creating control measures on breeding farms, the aim of this review was to know these reptiles and specially the Caiman crocodilus yacare and the helminth fauna of crocodiles, and its importance within the species breeding and to know the helminths fauna and the infections indicators of the crocodile Caiman crocodilus crocodilus from brazilian Amazon. Six animals were captured at the Tocantins-Araguaia basin, euthanized and necropsied on the field, with the opening and cleaning of each anatomical segment of the digestive tract. The contents obtained from washes were fixed in Railliet & Henry solution, to identification of helminths species and determination of the infections indicators. In total 652 helminths were gathered, from the six crocodiles necropsied, five of them nematodes species; Brevimulticaecum baylisi, Brevimulticaecum pintoi, Brevimulticaecum stekhoveni, Dujardinascaris longispicula, Dujardinascaris paulista, Contracaecum sp., one trematoda Proterodiplostomum globulare and one Acanthocephala, with larger percentage of infection for B. baylisi (83,3%) and larger abundance and mean intensity P. globulare with 91,6 and 274,5 respectively.